26. RESULTS OF CONSERVATIVE TREATMENT OF FOREARM BONES FRACTURE IN CHILDREN AT THE DEPARTMENT OF OUTPATIENT AT VIET DUC HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of conservative treatment of forearm bones fracture in children at the department of outpatient at Viet Duc Hospital from January 2023 to October 2023.Subjects and Methods: A prospective descriptive study was conducted on 202 children under 16 years of age, diagnosed with closed forearm bones fracture, treated conservatively by traction and cast at the Department of outpatient. Outcomes were assessed based on Anderson’s criteria.Results: The average age was 8.64 ± 3.5 years. The male-to-female ratio was approximately 2.4/1. The most common cause of injury was domestic accidents, accounting for 61% of cases. Conservative treatment yielded favorable outcomes, with excellent results in 85.1%, good results in 12.9%, fair results in 2%, and no poor outcomes. The most frequent complication was limited forearm supination and pronation (2%).Conclusion: Conservative treatment brings positive results.
Keywords: Forearm fracture; conservative treatment